Retinal Levels of Amyloid Beta Correlate with Cerebral Levels of Amyloid Beta in Young APPswe/PS1dE9 Transgenic Mice before Onset of Alzheimer’s Disease - Xi Mei; Mengxiang Yang; Lina Zhu; Qi Zhou; Xingxing Li; Zhongming Chen; Chenjun Zou (Behavioural Neurology)
Objectives. Retina abnormalities are related to cognitive disorders in patients with Alzheimer’s disease (AD). Retinal amyloid beta (Aβ) can be labeled by curcumin. We measured Aβ content in the cerebrum and retina of APPswe/PS1dE9 (APP) transgenic mice with early age to investigate the correlation between cerebrum and retina. Methods. APP mice and age-matched wild-type mice were investigated every month from age 2 months to 6 months to assess changes in Aβ content in the retina and cerebrum. At the beginning of each month, mice were fed a curcumin diet (50 mg/kg/day) for 7 consecutive days. The Aβ levels in the retina and cerebrum were measured by ELISAs. Correlations were identified between retinal and cerebral Aβ contents using Pearson’s correlation. Results. In the absence of curcumin, there was a significant correlation between Aβ contents in the retina and cerebrum of APP mice (r=0.7291, P=0.0014). With increasing age, Aβ-mediated degenerative change in the cerebrum (P<0.001 in 5 months) and retina (P<0.01 in 5 months) increased significantly. The inhibitory effect of curcumin on the Aβ level was significant in the cerebrum (P<0.001) and retina (P<0.01) of older APP mice in the early stage of life. Conclusion. We observed a significant correlation between the Aβ content in the retina and Aβ content in the cerebrum of APP mice. Our data suggest an appropriate time to measure retinal Aβ. Although curcumin can label Aβ in the retina, it also suppresses Aβ levels and weakens the degree of correlation between Aβ in cerebrum and retina tissues.